2016
DOI: 10.5966/sctm.2015-0231
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Mesenchymal Stromal Cell Transplantation Prevents Functional Bone Loss in a Mouse Model of Age-Related Osteoporosis

Abstract: This study shows that a single dose of minimally expanded mesenchymal stromal cells (MSCs) injected systemically into a mouse model of human age-related osteoporosis display long-term engraftment and prevent the decline in bone formation, bone quality, and microarchitectural competence. This work adds to a growing body of evidence suggesting that the decline of MSCs associated with age-related osteoporosis is a major transformative event in the progression of the disease. Furthermore, it establishes proof of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(45 citation statements)
references
References 63 publications
1
44
0
Order By: Relevance
“…It is particularly urgent to clarify the mechanism of stem cell differentiation and develop new strategies to induce stem cell differentiation. Recent advances have demonstrated that inducing mesenchymal stem cells differentiation into osteoblasts and promoting bone formation might be a new therapeutic approach 34,35 . Currently, hUC‐MSCs have been identified as promising sources of mesenchymal stem cells according to their capacity of self‐renewal, multipotency and low immunogenic properties 36 and better proliferative ability than other mesenchymal stem cells 37‐39 .…”
Section: Discussionmentioning
confidence: 99%
“…It is particularly urgent to clarify the mechanism of stem cell differentiation and develop new strategies to induce stem cell differentiation. Recent advances have demonstrated that inducing mesenchymal stem cells differentiation into osteoblasts and promoting bone formation might be a new therapeutic approach 34,35 . Currently, hUC‐MSCs have been identified as promising sources of mesenchymal stem cells according to their capacity of self‐renewal, multipotency and low immunogenic properties 36 and better proliferative ability than other mesenchymal stem cells 37‐39 .…”
Section: Discussionmentioning
confidence: 99%
“…More than 50% of periosteal cells are Sca‐1+; they showed osteogenic differentiation potential in vitro, and pro‐angiogenic ability in vivo . In addition, mice with global knockout of Sca1+ had an osteoporotic phenotype . Within a healing long‐bone defect, the distribution of these key progenitor populations is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…(25) In addition, mice with global knockout of Sca1þ had an osteoporotic phenotype. (26) Within a healing long-bone defect, the distribution of these key progenitor populations is still unclear. In addition, their responses to mechanical loading are virtually unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The deteriorating changes of bone in the OVX rats injected with saline was reflected by the thinning of the trabeculae, reduced bone surface area and bone volume in the proximal femur. These micro-structural changes are common problems in osteoporotic patients, causing fragility fractures (15,19). The small sample number of only 6 rats per group means that trends towards increased trabecular thickness in the femora of OVX rats injected with CXCR4 modified cells, were not clinically significant compared to untreated counterparts.…”
Section: Discussionmentioning
confidence: 99%